Haploidentical stem cell transplantation with post-transplant cyclophosphamide challenges and outcome from a tertiary care center in Lebanon - El Cheikh, Jean; Bidaoui, Ghassan; Sharrouf, Layal; Zahreddine, Ammar; Massoud, Radwan; Nehme, Rita; Kreidieh, Nabila; Moukalled, Nour; Abou Dalle, Iman; Mahfouz, Rami; Bazarbachi, Ali (Frontiers in Transplantation, 2023)
This letter describes the experience of the American University of Beirut Medical Center in Lebanon with haploidentical stem cell transplant (haplo-SCT) for hematological malignancies in adult patients. Haplo-SCT made it possible through universal and rapid donor availability for most of the adult patients with leukemia or lymphoma not only in the Middle East but also globally. Moreover, the use of post-transplant cyclophosphamide (PTCy) and reduced intensity conditioning (RIC) regimens when indicated improved the outcome and decreased the toxicity of haploidentical stem cell transplant. RIC regimens also allowed its use in the elderly population. Patients from throughout the Middle East come to our center, the American university of Beirut Medical Center, to receive this transformative type of stem cell transplant. In this paper, we discuss the results of haplo-SCT with PTCy done on adult patients with hematological malignancies in our center from 2015 to 2021. The results are encouraging and show that haplo-SCT should be considered more often in the Middle Eastern countries. The subgroup analysis showed the importance of achieving complete remission of the disease prior to transplant to improve outcomes in our center. There is a paucity of literature on the outcomes of haplo-SCT in the Middle East which may contribute to the limited number of centers that offer this type of SCT. Herein, we aim to fill this gap in the hopes of encouraging the implementation of this potentially curative modality of treatment to a larger extent in the Middle East.